Information Technology (IT) and Teacher-Talk-Time (TTT) in EFL Classes - Idapalapati, Srinivasa Rao (Journal of Education and Training, 2023)
Teacher-talk-time (TTT) if often considered a parameter of the effectiveness of an EFL teacher as TTT could relatively impact the student-talk-time (STT), which is considered quite essential in classroom discourses for better student outcomes. In view of the ascending importance of the quantum of TTT in EFL classes, and the ever-increasing integration of information technology (IT) in EFL teaching-learning settings, the present study explores the ways IT is being used to effectively reduce TTT and improve STT as well as the learning outcomes of the students. This study is driven by the assumption that IT supports EFL teachers a great deal in reducing their TTT in their classes. And the study aims at identifying the extent to which IT could support teachers in reducing their teacher talk and in facilitating more of their students’ talk. In addition, the study would draw inferences on the impact of the quantity and quality of teacher talk on the student talk as well as on the student outcomes. The study was carried out with the data gathered by employing mixed-methods approach that included that qualitative and quantitative methods together with the data collected from the relevant and existent literature online indirectly via the systematic approach together with the data gathered directly from the teachers of ELT at the Institute of Languages of the University of Tabuk through questionnaires and face-to-face interviews.